Web-oriented software for evaluation of the risk of enterprise bankruptcy - L. Yu. Huliailo; Yu. V. Tryus (Academy of Cognitive and Natural Sciences, 2015)
The aim of this work is to create web-oriented software for evaluation of the risk of enterprise bankruptcy. Research objectives: to analyze the most common methods of quantitative evaluation of the risk of bankruptcy; create a web-oriented software that implements quantitative methods for assessing the level of risk of bankruptcy online. The object of the study is quantitative methods for assessing the level of risk of bankruptcy. Subject of research is web-oriented software for evaluation of the risk of bankruptcy. The practical result is the creation web-oriented software that implements modern quantitative methods for assessing the level of risk of bankruptcy.